The Impact of Directive Leadership on Innovative Work Behavior: The Mediation Role of Continuance Commitment - Dhyah Mutmainnah; Tjutju Yuniarsih; Disman Disman; Janah Sojanah; Muji Rahayu; Iman Sidik Nusannas (Journal of Indonesian Economy and Business, 2022)
Introduction/Main Objectives: The aim of this study is to test the effect of directive leadership and continuance commitment on innovative work behavior while also explaining the mediating role of continuance commitment and the effect of directive leadership on innovative work behavior. Background Problems: Managing innovative employee behavior is an integral component of sustainable organizational development. Innovative work behavior (IWB) is very important for improving organizational performance. Many studies have identified the antecedent factors of IWB. Novelty: The novelty of this research is finding a new concept of innovative work behavior, through the combination of the mediation construct of continuance commitment, further established under the terms of "The Improvement Model of Innovative Work Behavior based on Directive Leadership through Integration Strategy by Continuance Commitment." Research Methods: This research’s design is hypothesis testing research and the type of research design it uses is survey research (non-experimental). This study uses the indicators from only one dimension of leadership and one organizational commitment category, so there are some empirical gaps between this and the results of previous studies. The sample in this study was 120 civil servants from PPPPTK TK and PLB Bandung. In assessing the empirical model this study used partial least square structural equation modeling (PLS-SEM) analysis. Finding/ Results: The results of this study show that directive leadership has a positive and significant impact on continuance commitment, and continuance commitment has a positive and significant influence on innovative work behavior. The effect of directed leadership on innovative work behavior is fully mediated by the continuance commitment, which is positively associated with innovative work behavior, but it is not significant. The influence of directive leadership on innovative work behavior is more favorable and significant as a result of the continuance commitment. Conclusion: This study concludes that directing leadership has an indirect effect on innovative work behavior through the mediating variable of continuance commitment, implying that directive leadership might indirectly promote innovative behavior through the continuance commitment. The assumption is that if a leader is effective at directing staff, there will be an increase in employees’ continuance commitment, and if commitment improves, there will be an increase in innovative work behavior.